How does creativity influence dishonest behavior? An empirical study of Chinese students. Issue 2 (17th February 2022) - Zhang, Chen; Wu, Jixia; Yang, Zhaoning; Perceval, Garon
ABSTRACT: This research aims to clarify the relationship between creativity and dishonesty. Study 1 (N = 74) examined whether creativity primed by the scrambled sentence test could influence dishonesty. The results showed that primed individuals were less likely to act dishonestly. Study 2 (N = 134) investigated the association between creative style and spontaneous (using a visual perception task) and instructed dishonesty (differentiation-of-deception paradigm). Rule-followers more often implemented spontaneous dishonest behavior but showed low accuracy in instructed lying tasks. The findings expand our understanding of the correlation between creativity and unethical behavior, which may improve moral creative talents.